Father figure : a novel - Peck, Richard, 1934- (New York : Viking Press, 1978)
After being a father figure for years, Jim and his younger brother are reunited with their divorced father and Jim is forced to find a new role for himself.
Wilson's Junior High School.
Wilson's Senior High School.
5.9
5.9
5-8
7-10.
Keywords: Brothers and sisters -- Fiction; Fathers and sons -- Fiction; Brothers and sisters -- Fiction; Divorce -- Fiction; Fathers and sons -- Fiction